Pengembangan Buku Cerita Predictable Book untuk Meningkatkan Kemampuan Berpikir Kritis Anak Usia Dini - Sulistia Arum Naningtias; Arwendis Wijayanti; Wening Sekar Kusuma (Early Childhood: Jurnal Pendidikan, 2023)
The purpose of this development research is to create a book "Predictable Books" which is valid, effective, efficient and interesting, to improve the critical thinking skills of children aged 4-5 years in Bringin sub-district. Critical thinking has an important role for AUD, the current phenomenon shows that the ability to think critically is a basic competency that is starting to be demanded along with the development of science and technology. Training generations to be able to think critically can become a strong foundation in the future. This type of research is research and development R&D (Research & Development) which refers to the ADDIE model with the stages of Analysis (Analyze), Design (Design), Development (Develop), Implementation (Implementation), and Evaluation (Evaluation). The results of this study are based on the results of validation on the aspects of effectiveness, efficiency, and attractiveness, through subject trials of material experts, media experts, small group trials involving 10 children in the Roudlotul Muttaqin KB and field trials involving 20 children in KB Shoots nation. Resulting in an assessment of 91.66% on the effectiveness aspect, 95% on the efficiency aspect, and 96.66% on the attractiveness aspect. This means that Predictable Books have a positive contribution and impact in improving the critical thinking skills of children aged 4-5 years in Bringin sub-district, Predictable Books are very effective as an alternative and supporting tool for teachers in an effort to improve the critical thinking skills of children aged 4-5 years.